Pengaruh Sarana Prasarana dan Disiplin Kerja Guru Terhadap Hasil Belajar Siswa Sekolah Dasar Negeri 119 Kota Palembang - Ika Lestari; Tri Widayatsih; Nurlina Nurlina; Zulfahmi Zulfahmi; Ika Wulandari (CV. ULIL ALBAB CORP, 2024)
A person's existence in the family, community, and country cannot be divorced from the importance of education. Enhancing student learning outcomes is one of the measures the government is taking to raise the standard of education in response to Indonesia's poor educational standards. The aim of this research is to determine and analyze the influence of infrastructure and teacher work discipline on student learning outcomes at SD Negeri 119 Palembang City. The sample in this research was 274 State Elementary School students in 119 Kota Palembang. The data collection method used in this research is a questionnaire with a Likert scale. The results of this research show that infrastructure has a significant effect on student learning outcomes at SD Negeri 119 Palembang City. This is proven by the results of the t test which shows that the calculated t value for the infrastructure and facilities variable is 2.244 which is greater than the t table of 1.660, (2.244 > 1.660) with The significance level of 0.026 is smaller than 0.05 (0.026 < 0.05). Work discipline has a significant effect on the learning outcomes of students at SD Negeri 119 Palembang City, this is proven by the results of the t test which obtained a calculated t value of 4.894 which is greater than the t table of 1.660, (4.894 > 1.660) with a significance level of 0.000 which is smaller than 0.05 (0.000 < 0.05 ). Infrastructure and work discipline have a positive and significant effect on the learning outcomes of students at SD Negeri 119 Palembang City, this is proven by the results of the F test which obtained calculated F values ​​> F table; 475,074 > 2.60 or α value, namely 0.000 < 0.05. For this reason, it is recommended that the Government be able to channel funds to schools to repair school buildings and provide facilities to support learning activities, so that students can study calmly and produce good achievements. Teachers are expected to be able to make good use of the facilities and infrastructure that have been provided and are willing to consciously carry out their duties and functions with full responsibility.